PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI INVENTARIS UNTUK MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PENGELOLAAN INVENTARIS DI INDAH JEJE SHOP - Dimas Alfiansyah; Ismarmiaty Ismarmiaty (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2026)
Manual inventory management remains a common problem among small and medium-sized retail businesses, including Indah Jeje Shop. The use of manual systems causes difficulties in monitoring stock availability, increases the risk of recording errors, and hinders the preparation of accurate and timely inventory reports. This study aims to design and implement a web-based inventory information system to improve the efficiency and effectiveness of inventory management at Indah Jeje Shop. The system development method used in this study is the waterfall method, which consists of requirements analysis, system design, implementation, and testing stages. The system was developed using the Laravel framework with a MySQL database and applies role-based access control consisting of superadmin, admin, and owner. The results of system testing using the black-box testing method indicate that all system functions operate properly and meet user requirements. Furthermore, the User Acceptance Testing (UAT) results show a user acceptance rate of 81%, which falls into the good category. Based on these results, it can be concluded that the developed web-based inventory information system is able to support inventory management processes in a more structured, accurate, and efficient manner.